Does Obesity Affect the Assessment of Third Trimester Amniotic Fluid? [1P]. Issue 1 (May 2017) - Andrikopoulou, Maria; Kinzler, Wendy; Calixte, Rose; Chavez, Martin; Fetsak, Galyna; Vintzileos, Anthony
Abstract : INTRODUCTION: To determine the inter-observer and intra-observer variability of amniotic fluid index (AFI) and maximum vertical pocket (MVP) measurements in obese pregnant women compared to non-obese pregnant. METHODS: This is a prospective study of women presenting for scheduled 3rd trimester clinically indicated ultrasound. AFI and MVP were measured by two sonographers. The first sonographer collected each measurement twice to assess intra-observer variability. The second sonographer was blinded to the measurement of the first sonographer to provide the measurement of inter-observer variability. Both measures of variability were estimated using the intra-class correlation (ICC) with 95% confidence intervals, ICC of 0.4 was considered the minimally accepted level of variability. All analyses were done using SAS 9.4®. RESULTS: Of the 126 patients enrolled, there was a mean maternal age of 33.8±5.5 years, mean BMI of 29.1±7.1 kg/m 2 and mean gestational age 32.9±0.9 weeks. At that time, 57.8% of the patients were obese, 20.6% of the patients were affected by gestational diabetes, and 19% of the patients had prior cesarean section. The mean BMI for obese patients was 36.9±5.6 kg/m 2 and for non-obese 26.5±2.8 kg/m 2 . ICC and 95% CI are presented for the overall cohort, as well as obese and non-obese women. CONCLUSION: Intra-observer variability for both MVP and AFI were acceptable in obese and non-obese women. Inter-observer correlation was poor, particularly when MVP was assessed in both obese and non-obese women. Obesity does not appear to have a significant impact on the variability of amniotic fluid assessment in the third trimester.